Analisa Pengetahuan Bencana Gunung Api dan Mitigasi pada Anak-Anak Panti Asuhan Adzkiyah Alkhair Kecamatan Denpasar Barat Provinsi Bali - Nia Maharani; Evi Dwi Krisna (UNIB Press, 2026)
This study is a continuation of a previous activity, namely a community service program conducted by the author and team, Community Service (PKM) in 2021 after the Covid-19 pandemic, held at the same location, Adzkiyah Alkhair Orphanage, West Denpasar District. The activity consisted of earthquake socialization and mitigation education using VR Box Reality. The current research focuses on volcanic disaster mitigation conducted at the orphanage, with the orphanage children as respondents. The respondents completed a questionnaire containing questions about the steps that should be taken before an eruption, during an eruption, and after a volcanic eruption occurs. The questionnaire results conclude that the orphanage children still lack knowledge regarding efforts to reduce the hazards of volcanic eruptions.